SAPHENOUS VEIN VS. SYNTHETIC GRAFT IN LOWER LIMB REVASCULARIZATION: A SIMPLE SUMMARY (CIPEEX, 2025)
Introduction: Surgical revascularization is essential in the treatment of critical limb ischemia. The most commonly used conduits are the autologous saphenous vein and synthetic grafts (ePTFE or HePTFE). The choice directly impacts the effectiveness and durability of treatment. Objective: To compare the clinical outcomes of autologous saphenous vein versus synthetic grafts in infrainguinal revascularization. Methodology: This is a literature review, with data sourced from the National Library of Medicine (PubMed) and MEDLINE, using the following descriptors: “Peripheral Arterial Disease,” “Critical Limb Ischemia,” “synthetic graft,” “ePTFE,” “HePTFE,” “saphenous vein,” “patency,” “limb salvage,” and “survival.” A total of 18 original studies in Portuguese and English, published between 2008 and 2023, were selected. These studies directly compared autologous saphenous vein and synthetic grafts in lower limb revascularization. Results: The saphenous vein demonstrated higher primary patency (78–79% at 12 months) and secondary patency (up to 70% at 5 years) compared to synthetic grafts (68–72% and up to 50%). Heparin-bonded prostheses showed intermediate performance. Complications such as infection and thrombosis were more prevalent in synthetic grafts. Conclusion: The autologous saphenous vein remains the gold standard for infrainguinal revascularization, with greater durability and fewer complications. Synthetic grafts, particularly HePTFE, are viable alternatives when the vein is unavailable, with favorable outcomes in selected cases.
Keywords: Revascularization; Saphenous vein; Synthetic graft; Peripheral arterial disease